2006
DOI: 10.1158/1078-0432.ccr-06-0110
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Activity of Cytotoxic Chemotherapy with Antiangiogenic Thrombospondin-I Peptides, ABT-526 in Pet Dogs with Relapsed Lymphoma

Abstract: Purpose: Thrombospondin-I (TSP-I) is a natural antiangiogenic protein that enhances apoptosis of activated endothelial cells. A modified nonapeptide fromTSP-I, ABT-526, has been found to be active in mouse cancer models and in dogs with naturally occurring cancers. To further assist in the development of ABT-526, we report herein on its evaluation in combination with cytotoxic chemotherapy in pet dogs with relapsed non-Hodgkin's lymphoma (NHL). Experimental Design: Ninety-four pet dogs with naturally occurring… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In the studies above the in vivo dosing of cytotoxic drugs was reduced to 1/20–1/50 of the maximally tolerated dose. Further studies demonstrated the validity of this approach: ABT-526 showed cooperative effect with cytotoxic agent lomustine (CeeNu, Bristol-Meyers-Squibb) in pet dogs with relapsed non-Hodgkin’s lymphoma [114] and with gemcitabine in the mouse model of pancreatic cancer [99, 115]. …”
Section: Tsp1 Based Therapies and Combinationsmentioning
confidence: 99%
“…In the studies above the in vivo dosing of cytotoxic drugs was reduced to 1/20–1/50 of the maximally tolerated dose. Further studies demonstrated the validity of this approach: ABT-526 showed cooperative effect with cytotoxic agent lomustine (CeeNu, Bristol-Meyers-Squibb) in pet dogs with relapsed non-Hodgkin’s lymphoma [114] and with gemcitabine in the mouse model of pancreatic cancer [99, 115]. …”
Section: Tsp1 Based Therapies and Combinationsmentioning
confidence: 99%
“…Canine non-Hodgkin's lymphoma has proven to be a relevant model for preclinical evaluation of new therapeutics for both initial induction and rescue of drug-resistant relapse (8)(9)(10)(11)(12)(13)(14). Evaluation of novel therapeutic approaches in dogs with spontaneous cancer offers potential benefit to canine patients and a rapid assessment of therapeutic index.…”
mentioning
confidence: 99%
“…8(1): 25-34 ________________________________________________________________________________________________________ (Knapp et al, 1992) Breast cancer BCG combined with surgery (Parodi et al, 1983) Immunotherapy (Teske et al, 1998) Non-Hodgkin's lymphoma Liposomal L-asparaginase (MacEwen et al, 1992) Antiangiogenic thrombospondin-I peptide (ABT526) (Rusk et al, 2006) Soft tissue sarcoma Antiangiogenic thrombospondin-I mimetic peptides (Sahora et al, 2012) Hyperthermia combined with irradiation (Gillette et al, 1992) Apart from these, canine osteosarcomas show overexpression of IL-8 and SLC1A3 which are related to poor outcome of human osteosarcoma . In a comparative study new genes (CDC5L, MYC, RUNX2 and CDKN2A/CDKN2B), that had not been described previously, were revealed in addition to genes (ADAM15, CTC1, MEN1, CDK7) with the known association in osteosarcoma (Angstadt et al, 2012).…”
Section: Http://wwwopenveterinaryjournalcom F Sultan and Ba Ganaiementioning
confidence: 99%